CRITICAL REVIEW ON THE IMPACT OF NURSING INTERVENTIONS ON PATIENT OUTCOMES IN INTENSIVE CARE UNITS IN A DEVELOPING COUNTRY - 1Hmoud Rabee Awad Albalawi, 2Hamda Salem Mubarak Alyami, 3Salma Musaed Alsaad, 4Amal Salem Mubarak Alyami, 5Noora Musaad Eid Al Najrani, 6Fatimah Ali Ahmad Alqaisi, 7Jamilah Essa Mohammed Assiri, 8Hadi Mushabbab Hadi Al Alharth, (Chelonian Research Foundation, 2022)
This review assesses the effect of nursing care in intensive care units (ICUs) on persistent results in developing nations. Through a comprehensive writing survey, the adequacy and impact of different viewpoints of persistent care within the serious care unit on persistent results were inspected. Strategies come about, and discoveries of important things are analyzed to get the suggestions for nursing care in developing nations. This article highlights the significance of nursing administrations in moving forward with persistent results in restricted settings. Furthermore, suggestions are given to progress healthcare in developing nations and eventually progress the care and results of seriously ill patients. Keywords: nursing interventions, intensive care units, patient outcomes, developing country, critical review